Choice reaction time and grip strength as predictors of cardiovascular mortality in middle‐aged and elderly Japanese: from the Radiation Effects Research Foundation Adult Health study - Shimizu, Masaki; Misumi, Munechika; Yamada, Michiko; Ohishi, Waka; Yamamoto, Hideya; Kihara, Yasuki (Internal medicine journal, 2018)
Background Cognitive function and physical function are important predictors of mortality. Aim To investigate whether or not reaction time (RT) as a cognitive function and grip strength (GS) as a physical function were associated, alone or in combination, with mortality from heart disease or stroke. Methods The subjects included 4901 Adult Health Study participants in Hiroshima who had undergone RT and GS measurements, were 35–74 years old at baseline (1970–1972) and were followed until the end of 2007. Results After adjustment for other potential risk factors, RT was positively and GS was negatively associated with mortality from both heart disease and stroke. These associations were persistent in the model when adjusting simultaneously for RT, GS and other factors, but hazard ratios were attenuated. When we evaluated the associations by baseline age and gender, we found the greater hazard ratios for RT in the younger cohort, but no clear modification by age for GS. The interaction between RT and GS was statistically significant (P = 0.012) for stroke mortality. In the stratified analyses divided using the age‐specific median value of RT or GS, the estimated hazard ratio of stroke mortality for RT was significant in participants with weak or strong GS but greater in the former, and for GS, it was only significant in participants with slow RT. Conclusion RT and GS, alone and in combination, predicted heart disease and stroke mortalities. Interventions for both cognitive function and physical function may be beneficial for the prevention of cardiovascular disease mortality.